Giors Boneto (1746-1828) e Paolo Soleri (1919 2013): un dialogo possibile - Catalina Golban (Annali Online dell'Università di Ferrara. Sezione Lettere)
What does it mean to inhabit a territory or to become aware of a territory? In a contemporary society, what significance is attributed to the sacred and how is it perceived or received by human beings? How can the experience of the religious man be transposed into modernity, or rather, into the life of contemporary (and naturally, Western) human beings? What connects a frescante and his 19th-century depictions nestled in the mountains of Val Maira with a 20th-century architect whose projects are primarily conceived for the Arizona desert? This study aims to offer an analysis of these questions.